A history of spine surgery predicts a poor outcome after hip arthroscopy. Issue 3 (20th July 2019) - Feingold, Jacob D; Heaps, Braiden; Turcan, Sava; Swartwout, Erica; Ranawat, Anil
Abstract: This study compared patient reported outcomes scores (PROMs) between patients undergoing hip arthroscopy who have and have not had previous lumbar spine surgery. We aimed to determine if prior spine surgery impacts the outcome of hip arthroscopy. Data were prospectively collected and retrospectively reviewed in patients who underwent hip arthroscopy between 2010 and 2017. Twenty cases were identified for analysis and matched to a control group. Four PROMs were collected pre-operatively and between 6 months and 2 years post-operatively (mean 16.2 months): Modified Harris Hip Score (mHHS), Hip Outcome Score-Activities of Daily Living (HOS-ADL), Hip Outcome Score-Sports (HOS-Sports) and the 33-item International Hip Outcome Tool (iHOT-33). Patients with previous spine surgery reported significantly worse ( P -value <0.001) post-operative scores on all PROMs and smaller net changes on all PROMs with the difference on the mHHS ( P -value 0.007), HOS-Sport ( P -value 0.009) and iHOT-33 ( P -value 0.007) being significant. Subsequent analyses revealed that the type of spine surgery matters. Patients with a spine fusion reported worse post-operative scores on all PROMs compared with patients with a spine decompression surgery with the difference on the mHHS ( P -value 0.001), HOS-ADL ( P -value 0.011) and HOS-Sport ( P -value 0.035) being significant. Overall, patients with prior decompression surgery experienced considerable improvements from hip arthroscopy whereas patients with a prior spine fusion reported poor post-operative outcomes. Given these results, it is vital that hip preservation surgeons understand the impact of the lumbar spine on the outcome of hip arthroscopy.